Lao People's Democratic Republic : Staff Report for the 2004 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2005)
The staff report for the 2004 Article IV Consultation on Lao People's Democratic Republic (PDR) highlights economic developments and policies. Lao PDR's recent macroeconomic performance has been relatively encouraging. Although some headway has been made in reforming the state banks and state-owned enterprises, progress in mobilizing revenues and strengthening expenditure management has been slow, owing to capacity constraints and difficulty in advancing reforms in a decentralized fiscal structure. IMF staff encouraged the authorities to maintain progress in restructuring the two state banks, as both banks remain vulnerable.